O liberalismo político de Isto É no processo da Assembléia Nacional Constituinte Brasileira nos anos de 1985 até 1988 - Marins, Priscila Marchini (2009)
The main purpose of this research is to investigate the ideological and political ideas of the magazine ISTO É. This research intends to understand how the magazine s position is and how it grew as a private device of hegemony. In order to achieve that, we analyzed the performance and political position of this weekly magazine considering the analysis of leads and articles of ISTO É about the accompaniment, the journalistic covering and news about the process of preparation, installation and approval of the Constituent National Assembly, between the period that extends into 1985 - beginning of the management of Jose Sarney and the guiding of the Constituent National Assembly - until 1988 - promulgation of the new Brazilian Constitution. The journalistic strategy and the practical hegemonic used by ISTO É magazine through its articles and editorials that had acted as political forces in the Brazilian society and the dispute with other means of communication have been studied in order to find out there were elements in the journalistic editorial that defended or directed proposals or measured neoliberal project already in that context of the decade of 1980